2010
DOI: 10.1111/j.1749-6632.2009.05329.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin reduces blood‐cerebrospinal fluid barrier permeability change, brain pathology, and functional deficits following traumatic brain injury in the rat

Abstract: Traumatic brain injuries (TBIs) induce profound breakdown of the blood-brain and blood-cerebrospinal fluid barriers (BCSFB), brain pathology/edema, and sensory-motor disturbances. Because neurotrophic factors, such as brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1), and glial cell-derived neurotrophic factor (GDNF), are neuroprotective in models of brain and spinal cord injuries, we hypothesized that a combination of neurotrophic factors would enhance neuroprotective efficacy. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…29 A previous study demonstrated that early intervention with Cerebrolysin reduces the BBB permeability and diminishes brain edema and other brain pathology, which contributes to recovery of sensorimotor function after TBI induced by a stab cerebral injury. 56 In the present study, Cerebrolysin treatment significantly increased the percentage of FITC-dextran-perfused vessels in the brain cortex, indicating that Cerebrolysin enhances the microvascular patency of the brain after CHI. This beneficial effect of Cerebrolysin may result from a combined action of multiple neurotrophic factors, such as CNTF, IGF-1, and GDNF.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…29 A previous study demonstrated that early intervention with Cerebrolysin reduces the BBB permeability and diminishes brain edema and other brain pathology, which contributes to recovery of sensorimotor function after TBI induced by a stab cerebral injury. 56 In the present study, Cerebrolysin treatment significantly increased the percentage of FITC-dextran-perfused vessels in the brain cortex, indicating that Cerebrolysin enhances the microvascular patency of the brain after CHI. This beneficial effect of Cerebrolysin may result from a combined action of multiple neurotrophic factors, such as CNTF, IGF-1, and GDNF.…”
Section: Discussionmentioning
confidence: 59%
“…Until now, only one preclinical study investigated the effects of acute Cerebrolysin treatment in a stab injury model of TBI in rats. 56 Closed head injury is the leading cause of death and disability in young patients in industrialized countries. 54 However, the efficacy of Cerebrolysin treatment for CHI has not been investigated.…”
mentioning
confidence: 99%
“…[17][18][19][20] Cerebrolysin has been shown to be safe and well-tolerated in clinical trials. 18,21,22 Cerebrolysin has important pharmacological actions that are relevant to its beneficial clinical effects, eg, promotion of synaptic regeneration, 23 improvement of neuronal survival, 24 protection of blood-brain barrier and blood-cerebrospinal fluid barrier, 25,26 and promotion of neural progenitor cell migration and neurogenesis. 27 Cerebrolysin given before spinal cord injury in rats reduced spinal cord water content, leakage of plasma proteins, and the number of injured neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrolysin is a mixture of neurotrophic factors and peptides that could act in the brain to attenuate oxidative or cellular stress [22,23]. The reduction in oxidative stress in TBI mediated by cerebrolysin appears to be one of the most important effects of the drug in terms of inducing neuroprotection [8].…”
Section: Discussionmentioning
confidence: 99%